1970
DOI: 10.1037/h0029970
|View full text |Cite
|
Sign up to set email alerts
|

Role of an unavoidability procedure in eliminating avoidance behavior with humans.

Abstract: interference is obligatory can never be complete, as all the manipulations that might increase it can never be assessed. The present experiment has shown that one such manipulation, the taxing of processing capacity, increases interference. If the effect is obligatory, however, any increase in judgment difficulty should be accompanied by an increase, or at least no decrease, in it. REFERENCES ATKINSON, R. C., & SHIFFKIN, R. M. Human memory; A proposed system and its control processes. In K. W.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
1

Year Published

1971
1971
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
(3 reference statements)
2
9
1
Order By: Relevance
“…In order to determine further the usefulness of tI~is interpretation, the present study varied the percentage of nonresponses followed by the NS in four groups: 0%, 25%, 75%, and 100%. Consistent with the methodology of Meyer (1970), human Ss received an air blast behind their right ear as the NS and learned a button depression as the AR. APPARATUS The apparatus consisted of a response button mounted on the right arm of a dental chair with a headrest, a pressurized-air delivery system with a 1/B-in.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…In order to determine further the usefulness of tI~is interpretation, the present study varied the percentage of nonresponses followed by the NS in four groups: 0%, 25%, 75%, and 100%. Consistent with the methodology of Meyer (1970), human Ss received an air blast behind their right ear as the NS and learned a button depression as the AR. APPARATUS The apparatus consisted of a response button mounted on the right arm of a dental chair with a headrest, a pressurized-air delivery system with a 1/B-in.…”
mentioning
confidence: 79%
“…66-67) have indicated the generally high resistance to extinction of an avoidance response (AR). In an effort to facilitate elimination of the persistent AR, Meyer (1970) found that human Ss stopped avoiding significantly faster with an unavoidability procedure than with normal extinction. The unavoidability procedure consisted of presenting the *This article is based on a thesis by the first author, which was supervised by the second and third authors and submitted to the Graduate School of the University of South Dakota in partial fulfillment of the requirements for the MA degree.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Bank (1965) reported that after 80 acquisition trials the most persistent group avoided for a mean of only 36 trials. Meyer (1970) and Drake and Meyer (1972) found that, after 40 training trials, subjects extinguished within 47 and 25 trials, respectively (also see Maxwell, Miller, & Meyer, 1971;Moffat & Koch, 1974). However, the Levis (1971) and Levis and Levin (1972) data suggest that extreme resistance to extinction is possible.…”
mentioning
confidence: 98%